Heat transfer performance of a radiator with and without louvered strip by using graphene-based nanofluids - M., Sandhya; D., Ramasamy; K., Sudhakar; K., Kadirgama; W. S. W., Harun (Yildiz Technical University, 2021)
The present work is focused on the Graphene-based nanofluids with high thermal conductivity which helps to improve the performance and enhance heat transfer. The thermal systems emphasis on the fluid coolant selection and statistical model. Graphene is a super-material, lighter than air, high thermal conductivity, and chemical stability. The purpose of the research is to work up with Graphene-based Nanofluids i.e., Graphene (G) and Graphene oxide (GO). Nanoparticles are dispersed in a base fluid with a 60:40 ratio Water & Ethylene Glycol and at different volume concentrations ranging from 0.01%-0.09%. Radiator model is designed in modelling software and louvered strip is inserted. The simulation (Finite Element Analysis) is performed to evaluate variation in temperature drop, enthalpy, entropy, heat transfer coefficient and total heat transfer rate of the considered nanofluids, results were compared by with and without louvered strip in the radiator for the temperature absorption. 58-60% enhancement of enthalpy observed when Graphene and Graphene oxide nanofluid was utilized. 1.8% enhancement of entropy is observed in 0.09% volume concentration of the Graphene and Graphene oxide nanofluid when louvered strips are inserted in the radiator tube at a flow rate of 3 LPM. With louvered strip inserted in the radiator, heat transfer coefficient enhanced by 236% for Graphene and 320% enhancement is identified for Graphene oxide nanofluid when compared to without louvered strip insert. The results stated that high performance is observed with the utilization of louvered strip in the radiator tube.